1980
DOI: 10.1177/030098588001700504
|View full text |Cite
|
Sign up to set email alerts
|

Canine Hepatic Neoplasms: A Clinicopathologic Study

Abstract: Abstract. One hundred ten primary hepatic neoplasms, excluding hematopoietic and vascular tumors, were diagnosed in 12,245 canine necropsies. Included were 55 hepatocellular carcinomas, 24 bile duct carcinomas, 2 combined hepatocellular and cholangiocarcinomas, 15 carcinoids and 14 sarcomas. A majority of the dogs with hepatocellular carcinoma (80%), bile duct carcinoma (65%) and sarcoma (61%) were 10 years old or older; 71% of the dogs with carcinoid were under 10 years old. Hepatocellular carcinoma and sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
183
1
15

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(210 citation statements)
references
References 17 publications
11
183
1
15
Order By: Relevance
“…Transitional carcinoma of the respiratory epithelium is infrequently reported in dogs (Patnaik, 1989;Wilson and Dungeword, 2002;Lopez, 2007). The term transitional carcinoma is recommended by the World Health Organization for this kind of tumor in dogs (Dungworth et al, 1999), despite sometimes being reported as respiratory epithelial carcinoma, non-keratinizing squamous cell tumor or undifferentiated carcinoma (Dungworth et al, 1999;Wilson and Dungword, 2002;Caswell and Williams, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Transitional carcinoma of the respiratory epithelium is infrequently reported in dogs (Patnaik, 1989;Wilson and Dungeword, 2002;Lopez, 2007). The term transitional carcinoma is recommended by the World Health Organization for this kind of tumor in dogs (Dungworth et al, 1999), despite sometimes being reported as respiratory epithelial carcinoma, non-keratinizing squamous cell tumor or undifferentiated carcinoma (Dungworth et al, 1999;Wilson and Dungword, 2002;Caswell and Williams, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sci. 68 (7): [765][766][767] 2006 Hepatocellular carcinoma (HCC), the most common primary liver tumor in dogs [7,8], has previously been reported to be associated with hypoglycemia as paraneoplastic syndrome in a dog [6]. In general, hypoglycemia of non-islet cell tumors such as HCC is improved by resection and reappears after recurrence of a tumor [6].…”
mentioning
confidence: 99%
“…In these non-islet cell tumors, the serum insulin concentration is low in dogs [1,3,8,10]. Hypoglycemia is detected in these tumors, which are generally very large and found in the abdominal cavity.…”
mentioning
confidence: 99%
“…Alguns desses agentes químicos seriam os peptídios e as citocinas (FOLKMAN et al, 1971). A angiogênese normal ocorre durante o desenvolvimento embrionário e na vida adulta normal, durante a ovulação e a cicatrização de feridas (CERRI; MÓLNAR; VEZOZZO, 1998 PAITNAIK et al, 1980;STRAW, 1996). O exame ultra-sonográfico é uma técnica extremamente útil na avaliação hepática quando da suspeita de neoplasias primárias ou metastáticas (WHITELEY et al, 1989).…”
Section: 1unclassified
“…O tumor benigno dos hepatócitos é denominado adenoma hepatocelular (ou hepatoma), enquanto o tumor maligno epitelial é denominado carcinoma hepatocelular. O carcinoma hepatocelular é a neoplasia maligna primária hepática mais comum em cães (HAMMER; SIKKEMA, 1995;PAITNAIK et al, 1980;STRAW, 1996). Em relação às neoplasias linfóides que acometem o fígado, o linfoma é predominante em animais da espécie felina e, embora se acredite que a mesma prevalência ocorra em cães, nem sempre o parênquima hepático de cães com linfoma é biopsiado (HAMMER; SIKKEMA, 1995).…”
Section: Origem Hepáticaunclassified